Correlations between depression behaviors and sleep parameters after repeated corticosterone injections in rats - WANG Zi-jun; YU Bin; ZHANG Xue-qiong; SHENG Zhao-fu; LI Sheng-jie; HUANG Yuan-li; CAO Qing; CUI Xiang-yu; CUI Su-ying; ZHANG Yong-he (Acta Pharmacologica Sinica, 2016)
Zi-jun WANG, Bin YU, Xue-qiong ZHANG, Zhao-fu SHENG, Sheng-jie LI, Yuan-li HUANG, Qing CAO, Xiang-yu CUI, Su-ying CUI, Yong-he ZHANG* Department of Pharmacology, Peking University, School of Basic Medical Science, Beijing 100191, China Aim: Disrupted sleep may be a prodromal symptom or a predictor of depressive disorders. In this study we investigated the relationship between depression symptoms and disrupted sleep using a novel model of stress-mimicked sleep disorders in rats. Methods: SD rats were injected with corticosterone (10, 20 or 40 mg/kg, sc) or vehicle for 7 d. Their sleep-wake behavior was monitored through implanted EEG and EMG electrodes. Their depressive behaviors were assessed using forced swim test, open field test and sucrose preference test. Results: The corticosterone-treated rats showed significantly reduced sleep time, disinhibition of rapid-eye-movement (REM) sleep and altered power spectra during non-REM sleep. All depressive behavioral tests did not show significant difference across the groups. However, individual correlation analysis revealed statistically significance: the immobility time (despair) was negatively correlated with REM sleep latency, slow wave sleep (SWS) time ratio, SWS bouts and delta power density, and it was positively correlated with REM sleep bouts and beta power density. Meanwhile, sucrose preference (anhedonia) was positively correlated with total sleep time and light sleep bouts, and it was negatively correlated with the REM sleep time ratio. Conclusion: In stress-mimicked rats, sleep disturbances are a predictor of depressive disorders, and certain symptoms of depression may be related to the disruption of several specific sleep parameters. Keywords: depression; sleep; corticosterone; stress; EEG; open field test; forced swim test; sucrose preference test This study was funded by grants from the National Natural Science Foundation of China (No 81173031, 81202511 and 81302746). * To whom correspondence should be addressed. E-mail zhyh@hsc.pku.edu.cn Received 2014-03-08 Accepted 2014-05-20